CHEMICAL INDUSTRY OF RUSSIA: CURRENT STATE AND DEVELOPMENT PROBLEMS - E. V. Kulyasova (Вестник университета, 2019)
An overview of the chemical industry of the Russian Federation at present stage has been adduced, the main economic indicators of its industries have been analyzed. The position of the Russian chemical complex in the world market of chemical products has been studied. The main problems of development of the chemical complex of Russia, as well as existing external and internal barriers have been revealed. Taking into account the analysis of the state of the chemical industry in developed countries, the priority areas and tools for the development of the chemical complex of Russia have been considered. Special attention has been paid to the development of innovative component and to the implementation of digital technologies at the enterprises of the chemical complex.